To Whom Would You Recommend as an Excellent Community Nurse? Guidelines for Nursing Education Based on Paradigmatic Nurse Life Histories [¿A Quién Recomendarías Como Excelente Enfermera Comunitaria? Orientaciones Para la Formación en Enfermería a Partir de Las Historias de Vida de Enfermeras Paradigmáticas] - Pasmanik-Volochinsky, D (Elsevier Espana S.L.U, 2020)
Objectives: To reconstruct the biographical account of community nurses, acknowledged by their peers as highly reputed, and to describe their characteristic attributes; to search for guidelines to optimise training in nursing at community level according to their experience. Method: Biographical narrative method (life history) under the constructivist paradigm. Three nurses, chosen unanimously by significant peers as excellent nurses, were interviewed by means of in-depth interviews. The resulting texts were analysed using two qualitative content analysis procedures that contribute to the comprehension of the representation of an exemplar community nurse, a) data categorisation from a time perspective, and b) categorise the content of the interviewed attributes and their perspectives and practices as regards nursing education. Results discussion and conclusions: The results show a homogeneous representation of being a nurse, highlighting the traditional subjects of a caring vocation, a sense of ethics, and courage. At the same time, is an autonomous professional, a leader that conceives his/her job as systemic. It is remarkable to find accounts of psychological undermining as consequence of conflicts with authoritarian head nurses and the unanimous criticism of the social conditions. They attribute to the neoliberal economy, nevertheless they omit the political dimension in their arguments. As regards nursing education, they consider humanized nursing and a reflective practice as essential. In view of these results, it is suggested, from the point of view of ethics of care, that a proposal on the concept of mature care should be included in nursing education that might promote ethic reflection in current social conditions. © 2018 Elsevier España, S.L.U.